Differentiated Impacts of Indoor and Outdoor Fitness Environments on Residents’ Activity Intensity: A Perspective on Homo Urbanicus - Wei Wei; Wenyi Xu; Mengyao Hong (Buildings)
This study develops a framework for the impact mechanism based on the “homo urbanicus” theoretical perspective, linking indoor and outdoor fitness environmental elements to residents’ subjective perceptions and their activity intensity. An empirical investigation is conducted using structural equation modeling (SEM) with data from 286 valid questionnaires (N = 421). The results demonstrate that both indoor and outdoor fitness environmental elements—specifically spatial, facility, and environmental factors—significantly positively influence residents’ fitness activity intensity, with this relationship mediated by perceptions of safety, convenience, comfort, and aesthetics. Furthermore, the study uncovers variations in the types and degrees of influence across indoor and outdoor settings. Based on these findings, the author proposes several planning and design strategies: “In indoor environments, it is essential to ensure that fitness spaces feature bright lighting and thoughtful design to enhance aesthetic appeal; additionally, optimizing spatial layouts and integrating information services can foster greater social interaction. For outdoor environments, prioritizing locations near aesthetically pleasing architecture, adjacent to blue landscapes, and within open areas, as well as sites that are close to community amenities and abundant surrounding facilities, will enhance residents’ fitness activity intensity”.